Evaluation of the ThroLy score for the prediction of venous thromboembolism in newly diagnosed patients treated for lymphoid malignancies in clinical practice. (15th May 2018) - Rupa‐Matysek, Joanna; Brzeźniakiewicz‐Janus, Katarzyna; Gil, Lidia; Krasiński, Zbigniew; Komarnicki, Mieczysław
Abstract: The utility in clinical practice of a recently developed and validated predictive model for venous thromboembolism (VTE) events in lymphoma patients, known as the thrombosis lymphoma (ThroLy) score, is unknown. We evaluated the association of ThroLy with VTE in patients treated for diffuse large B‐cell lymphoma (DLBCL) or Hodgkin lymphoma (HL) undergoing ambulatory first‐line chemotherapy. Retrospective analyses were performed on 428 patients (median age 50), 241 were newly diagnosed DLBCL, and 187 had HL. During initial chemotherapy, 64 (15%) patients developed VTE. According to the ThroLy, 322 (75.2%) patients were considered low risk, 88 (20.6%) patients had intermediate risk and 18 (4.2%) patients high risk for VTE development. Patients with DLBCL were more often in the high‐risk ThroLy group and had more VTE events than HL. VTE occurred in; 38.9% (n = 7) high‐risk patients, 29.5% (n = 26) intermediate risk, and 9.6% (n = 31) low risk according to the ThroLy score. However, in multivariate analysis, high ThroLy (OR 5.13; 95% CI: 1.83‐14.36, P = .002), intermediate ThroLy (OR 3.96; 95% CI: 2.19‐7.17, P < .001), and aggressive lymphoma‐DLBCL (OR 1.91; 95% CI: 1.05‐3.47, P = .034) were all significantly associated with development of VTE, 48% of the VTE events occurred in the low‐risk ThroLy score group (the ROC AUC (95% CI) 0.40‐0.70 and C statistic‐0.55). In our study, the ThroLy score was not a suitably accurate model for predicting VTE events in patients at higher risk of VTE. Further research should be conducted to identify new biomarkers that will predict these events and to establish a new VTE risk assessment model. Abstract : Accuracy of Thrombosis Lymphoma (ThroLy) in predicting VTE events in lymphoma patients is not defined. Although, in multivariate analysis, high ThroLy (>3 points), intermediate ThroLy (2‐3 points), and aggressive lymphoma‐DLBCL were all significantly associated with VTE development, 48% of VTE events occurred in the low‐risk ThroLy group (C statistic‐0.55). In our study, the ThroLy score was not a suitably accurate model for predicting VTE events in patients at higher risk of VTE.